Evaluation of the vibration performance response of insulating floor panels under human walking conditions - Opazo Vega, Alexander; Dechent Anglada., Peter; Cendoya Hernandez, Patricio; Molina Vicuña, Cristian (Revista de la Construcción. Journal of Construction, 2016)
The use of lightweight prefabricated floor panels has grown considerably over the last two decades. Previous studies have shown a detrimental vibrational response of these floors under human walking conditions, resulting in user complaints. The present study evaluates the vibration performance of a newly developed construction system in Chile, composed of deck‐type insulating floor panels installed in dwellings constructed with ferro‐cement prefabricated construction panels. The vibrations induced by walking steps were measured in 36 dwellings of three different models. Individual synchronized walks were performed at different step frequencies with individuals of different weights. For the evaluation, the serviceability criteria and vibration performance indicators proposed in the ISO 10137 standard were used. The results show that the floor panels have an impulsive vibration response with average vertical natural frequencies of 26.14 Hz and damping ratios of 4.3%. In the dwellings with a lower damping ratio, the performance indicators presented unfavorable values when the heaviest individuals walked at the greatest step frequency. If the serviceability criteria are implemented, it is predicted that 97.22% of the floor panels will not generate significant user discomfort, validating the construction system.